Fundamentos del tribunal constitucional para anular las resoluciones del jurado nacional de elecciones - Adrianzén Carreño, Javier Ildefonso (2015)
The jurisprudence oh the Constitutional Court (TC) on electoral matter was studied in this research in order to determine the fundamentals to annul the resolutions of the National Jury of Elections (JNE) – despite this electoral entity is autonomous and independent – in accordance with the Political Constitution. Methods of analysis, synthesis, hermeneutics and comparison were applied for the study of legislation, doctrine and jurisprudence on the roles of the TC and JNE. The techniques of document analysis on resolutions of the TC and JNE, the use of index cards as well as constitutional legislation related to the subject-study were used to collect data. A documentary record sheet, bibliographic and summary index cards were used as data collections tools. The evidence was composed by three resolutions of the TC on actions for the protection of constitutional rights filed against the JNE and a resolution of the JNE that ceased Mr. Arturo CASTILLO CHIRINOS, Mayor of Chiclayo. This last resolution was subsequently annulled by the TC through an action for the protection of constitutional rights because of the violation of fundamental rights. It was concluded that the main grounds of the TC to annul the resolutions of the JNE were the following: When the JNE acts beyond the jurisdictions delimited in the Constitutions dealing with matters other than electoral ones; in the cases that the resolutions of the JNE are biased with nullity due to the violation of principles and fundamental rights, such as the principle of separation of powers, innocence and independence in the exercise of the jurisdictional function, and the violation of fundamental rights of those who claim to participate in the political life of the country and be elected; the observance of due process, and because the JNE disregarded the TC as a supreme interpreter of the Constitution and, therefore, the JNE is not exempted from the control over its decisions.